PENGARUH TERAPI BERMAIN LEGO TERHADAP INTERAKSI SOSIAL ANAK AUTIS DI SDLB 017700 KISARAN NAGA KECAMATAN KISARAN TIMUR KABUPATEN ASAHAN TAHUN 2019 - Dewi Tiansa Barus; Citra Anggraini; Friska Sembiring (Jurnal Penelitian Keperawatan Medik, 2020)
Social interaction is a relationship relating to individuals with individuals, individuals with groups, and groups with groups in which there is cooperation and competition. Children with autism have language and communication difficulties as well as understanding their surroundings. Researchers have the aim to determine the effect of lego play therapy on the social interactions of children with autism. In this study, researchers used a pre-experimental research design in the form of one group pretest-posttest. The sample in this study were all students suffering from autism, as many as 13 students in grades 1 - 4, with age 7 - 10 years with total sampling technique. Collecting data using observation sheets, researchers wanted to find out the extent to which play lego therapy can increase social interaction in children with autism. Where the results of the study state social interaction before being given lego play therapy is 1.15, while after being given lego play therapy is 1.77 . The results of statistical tests that have been conducted by researchers say there is an effect of lego play therapy on social interactions of children with autism can be seen the results of the p-value < 0.05. In this case the researchers suggest that teaching staff at SDLB in the future be able to implement this lego play therapy so that the social interaction of children with autism can increase even better.